2006
DOI: 10.1002/cncr.21667
|View full text |Cite
|
Sign up to set email alerts
|

The effect of menatetrenone, a vitamin K2 analog, on disease recurrence and survival in patients with hepatocellular carcinoma after curative treatment

Abstract: BACKGROUNDThe high recurrence rate of hepatocellular carcinoma (HCC) determines the long‐term prognosis for patients with HCC. In the current study, the authors tested the effects of menatetrenone, a vitamin K2 analog, on recurrent HCC and survival after curative treatment.METHODSSixty‐one patients who were diagnosed as free of HCC after surgical resection or percutaneous local ablation were assigned randomly assigned to either a menatetrenone group (n = 32 patients) or a control group (n = 29 patients). Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
120
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(125 citation statements)
references
References 46 publications
5
120
0
Order By: Relevance
“…The safety, relatively low cost, and ease of use make vitamin K 2 a suitable candidate for clinical trials that assess the value of combination of chemoprevention or chemotherapy in at-risk patients or in patients with a confirmed diagnosis of HCC [116,[122][123][124][125].…”
Section: Vitamin Kmentioning
confidence: 99%
See 2 more Smart Citations
“…The safety, relatively low cost, and ease of use make vitamin K 2 a suitable candidate for clinical trials that assess the value of combination of chemoprevention or chemotherapy in at-risk patients or in patients with a confirmed diagnosis of HCC [116,[122][123][124][125].…”
Section: Vitamin Kmentioning
confidence: 99%
“…Vitamin K 2 was reported to inhibit HCC development among female patients with cirrhosis, who had received the vitamin for the prevention of osteoporosis [122]. A small RCT suggested that vitamin K 2 was effective in suppressing HCC recurrence and may improve survival [124]. However, subsequent, large-scale RCT met with an early termination because of lacking evidence of effects.…”
Section: Tertiary Prevention Of Hcv-related Hccmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of vitamin K in bone metabolism is further supported by studies showing that vitamin K inhibits osteoclastic bone resorption by induction of osteoclast apoptosis [13,14]. In addition to these biological activities, vitamin K 2 has been reported to induce apoptosis in hepatocellular carcinoma, leukaemia [15] and myelodysplastic syndrome cell lines [16].…”
Section: Introductionmentioning
confidence: 98%
“…Recently VK2 also was found to inhibit hepatoma cell invasiveness and metastasis (11). More importantly, we recently demonstrated that administration of VK2 to HCC patients significantly decreased recurrence of HCC after curative local ablation therapy (12). Habu et al (13) reported that VK2 suppressed development of HCC from the cirrhotic liver in patients infected with hepatitis virus.…”
Section: Introductionmentioning
confidence: 96%